The effect of solvents on ZnS nanostructures synthesized by biomolecule-assisted solvothermal method - Kaowphong S. (2014)
Nanostructured ZnS (hexagonal and cubic) were synthesized by a 200 °C and 24 h solvothermal reaction of Zn (CH3COO)2· 2H2O and L-cysteine (C3H7NO2S) in water, propylene glycol (PG) and glycerol (GR) solvents. The products, characterized by XRD, were specified as pure ZnS (hexagonal) in water, and ZnS (cubic) in PG and GR. SEM and TEM analyses showed the particle sizes and agglomerated behaviors, mainly related to the reaction media, which were in accordance with BET adsorption of nitrogen, with blue shift energy gaps relative to the bulk. © 2011 Elsevier B.V. All rights reserved.